Penyuluhan Persiapan Laktasi di Wilayah Kerja Puskesmas Cibeureum Kota Tasikmalaya dengan Menggunakan Media Lambung Bayi Plastisin - Irianti, Bayu; Mardiah, Siti Saadah; Silalahi, Uly Artha (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2021)
One of the problems in child in Indonesia is Stunting. The high number of stunting in Indonesia need specific attention, its about 27.9% in 2019. Exclusive breastfeeding became one of the factors to determin stunting. The number of exclusive breastfeed in west java its about 73.1, Tasikmalaya only reach about 67.63% its still low than the Weast Java Target. (dinkes tasik,2020; BPS,2020) the pilot study in 5 pregnant women showed that 4 women didn’t anggage in giving Breasfteed to her baby because the baby still cries event they give brest milk (still hungry).the plasticine models could help them about the zise of the baby stomach, so the target of exclusive breastfeeding became a rising and the number of drop out will be decrease, especially at Primery health care of Cibeureum.